Quantum Mechanics - María Cetto, Ana; de la Peña, Luis (Cambridge University Press, 2026)
Intended as a companion to undergraduate and graduate courses in quantum mechanics, this textbook uses an intuitive conceptual framework grounded in the physical explanation of quantum phenomena. This title is also available as Open Access on Cambridge Core.